Portugal and Brazil - Malamud, A.; Seabra, P. (The Oxford handbook of Portuguese politics, 2022)
Relations between Portugal and Brazil are often characterized as much by political ambiguity as by a rhetoric that oscillates between fraternity in public speech, and condescendence in private conversation. These features can be found at the core of every advance and obstacle in the institutionalization of this bilateral relationship, and they help to explain the particularities of the political bond between Lisbon and Rio (initially) or Brasília (later). This chapter compares parallel political developments within both countries and highlights points of contention and attraction between the two countries. The chapter is divided chronologically into four sections: colonial rule; the Estado Novo regimes; the end of both dictatorships; and the democratic period. By exploring contrasts, similarities and reciprocal influences, we suggest that historical linkages have worked as a buffer rather than a driver towards a substantive common agenda.